Investigation of Reasons for Preferring Small Houses Built in Konya - Kerim Çınar; Hatice Çınar (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Today, as a result of the changes in social, cultural and family life with globalization, the demands and needs of people have also changed. Due to reasons such as changes in lifestyle, shrinkage in the family, individualization and single-person living style, residences have been reduced spatially and the production of 'studio flats', the most common types of small residences produced as 1+0, 1+1, 2+1, has increased today. The focus of this study is the suitability of the small housing users produced in Konya to their lifestyles and why they prefer these houses. In the study, it is assumed that there will be differences in small housing type selections and small housing features according to the demographic characteristics of small housing users. Based on this assumption, a questionnaire was applied to 259 small house users in a studio-type house in the Selçuklu district of Konya. As a result of the research, it has been determined that single users mostly prefer 1+1 flat types, while married individuals prefer 2+1 flat types. It has been observed that as the number of households in the residence increases, the demand for 2+1 duplex flats increases. In addition, it has been determined that the users attach importance to the safety in the house according to the location of the house and their gender according to their marital status. It is thought that the results obtained from this study will guide designers and housing manufacturers at the beginning of small housing design by revealing the expectations and preferences, attitudes and behaviors of small housing users.